Signifikansi Konsep Ketuhanan Yang Maha Esa bagi Umat Buddha di Tangerang - Madiyono Madiyono (Jurnal Pelita Dharma, 2019)
This research was initiated by the tendency for the increasing tendency of religious communities in Indonesia to accentuate their religious identity to external communities, even into the political sphere by raising sensitive issues. One of the things that is quite sensitive related to religion is the problem of Godhead. Buddhism has a different God concept from other religions. However, the concept of the Godhead of Buddhism is often perceived as incompatible with the first principle of the Pancasila, even some Buddhists are hypothesized of not understanding the concept of the Godhead. This study aims to determine the significance of the level of understanding of the people about the concept of Godhead that is in harmony and not in harmony with Buddhism. Data collection is done through a questionnaire instrument with a choice of statements on a modified Likert scale. The collected data was then grouped and analyzed by calculating the percentage of the suitability and incompatibility of the concept of Godhead in Buddhism. The results showed that the concept of Godhead in Buddhism was believed and important for Buddhists in Tangerang. The significance level of Buddhists' understanding of the Godhead in Buddhism is 64%. Some aspects of the Godhead in accordance with the teachings of Buddhism are perceived by most Buddhists in Tangerang, namely the concept of something that is not born, is not created, is not incarnate, is not tangible, one, holy, does not play a direct role in regulating life, not regulating nature, not the cause of the diversity of beings, not regulators of destiny, is not the answer to prayer. According to the Divine Godhead, Buddhism is different from God in other religions, but does not conflict with Pancasila. Indonesian Buddhists, especially in Tangerang, also affirm that they are not followers of Atheism.Penelitian ini diawali oleh adanya tendensi meningkatnya kecenderungan umat beragama di Indonesia untuk menonjolkan identitas keagamaannya ke pihak eksternal, bahkan sudah masuk ke ranah politik dengan memunculkan isu-isu sensitif. Salah satu hal yang cukup sensitif berhubungan dengan agama yaitu masalah Ketuhanan Yang Maha Esa. Agama Buddha memiliki konsep Ketuhanan yang berbeda dengan agama lainnya. Namun, konsep Ketuhanan dalam agama Buddha seringkali dipersepsikan tidak sesuai dengan sila pertama Pancasila, bahkan sebagian umat Buddha diduga belum memahami konsep Ketuhanan tersebut. Penelitian ini bertujuan untuk mengetahui signifikansi tingkat pemahaman umat mengenai konsep Ketuhanan Yang Maha Esa yang selaras dan tidak selaras dengan ajaran Buddha. Pengumpulan data dilakukan melalui instrumen kuesioner dengan pilihan pernyataan dalam skala Likert yang dimodifikasi. Data yang dikumpulkan kemudian dikelompokkan dan dianalisis dengan menghitung persentasi tingkat kesesuaian dan ketidaksesuaian konsep Ketuhanan Yang Maha Esa dalam agama Buddha. Hasil penelitian menunjukkan konsep Ketuhanan Yang Maha Esa dalam Agama Buddha merupakan hal yang diyakini dan penting bagi umat Buddha di Tangerang. Signifikansi tingkat pemahaman umat Buddha mengenai Ketuhanan Yang Maha Esa dalam agama Buddha yaitu 64%. Beberapa aspek mengenai Ketuhanan Yang Maha Esa yang sesuai dengan ajaran Buddha yang dipersepsikan oleh sebagian besar umat Buddha di Tangerang yaitu konsep ada sesuatu yang tidak dilahirkan, tidak tercipta, tidak menjelma, tidak berwujud, esa, suci, tidak berperan langsung mengatur kehidupan, bukan pengatur alam, bukan penyebab keragaman makhluk, bukan pengatur takdir, bukan pengabul doa. Menurut umat Buddha, Ketuhanan Yang Maha Esa dalam agama Buddha berbeda dengan Ketuhanan dalam agama lain, tetapi tidak bertentangan dengan Pancasila. Umat Buddha Indonesia, khususnya di Tangerang juga menegaskan bukan penganut ateisme.